ANALISIS PERBEDAAN ABNORMAL RETURN, TRADING VOLUME ACTIVITY DAN TRADING FREQUENCY SEBELUM DAN SESUDAH PENGUMUMAN MENTERI KABINET KERJA (Event Study pada Saham LQ-45 di Bursa Efek Indonesia) - Lina, Rosa; Halim, Abdul; Made, Anwar (Jurnal Riset Mahasiswa Akuntansi, 2015)
The purpose of this study was to analyze the difference in average abnormal return, trading volume activity, and trading frequency before and after the announcement of the Minister of Working Cabinet. This study is an event study of the 45 stocks of companies included in the LQ-45 period August 2014 to January this 2015. This study used observation period 5 days before and 5 days after the announcement of the Working Cabinet. This study used secondary data obtained from the Indonesian Stock Exchange (IDX). The data used in this study include the closing price, volume, and frequency and listed share. Data analysis techniques for hypothesis testing using paired samples t-test. Based on the analysis showed that there was no difference in the average abnormal return, the average trading volume activity, the average trading frequency both before and after the announcement of the Working Cabinet.